Theorizing Fieldwork in the Humanities Methods, Reflections, and Approaches to the Global South - Puri, Shalini; Castillo, Debra A.; SpringerLink (Online service) (New York : Palgrave Macmillan US(Imprint), 2016)
This volume, the first of its kind, launches a conversation amongst humanities scholars doing fieldwork on the global south. It both offers indispensable tools and demonstrates the value of such work inside and outside of the academy. The contributors reflect upon their experiences of fieldwork, the methods they improvised, their dilemmas and insights, and the ways in which fieldwork shifted their frames of analysis. They explore how to make fieldwork legible to their disciplines and how fieldwork might extend the work of the humanities. The volume is for both those who are already deeply immersed in fieldwork in the humanities and those who are seeking ways to undertake it. .
1. Debra A. Castillo and Shalini Puri, Introduction: Conjectures on Undisciplined Research -- 2. Shalini Puri, Finding the Field: Notes on Caribbean Cultural Criticism, Area Studies, and the Forms of Engagement -- 3. Naminata Diabate, Women's Naked Protest in Africa: Comparative Literature and its Futures -- 4. Kavita Panjabi, Aesthetics in the Making of History: The Tebhaga Women's Movement in Bengal -- 5. Jennifer Lynn Kelly, Locating Palestine within American Studies: Transitory Field Sites and Borrowed Methods -- 6. Neil Doshi, Absent Performances: Distant Fieldwork on Social Movement Theater of Algeria and India -- 7. Tori Holmes, Ethical Dilemmas in Studying Blogging by Favela Residents in Brazil -- 8. Rashmi Sadana, Reading Delhi, Writing Delhi: An Ethnography of Literature -- 9. Lara Putnam, Daily Life and Digital Reach: Place-Based Research and History's Transnational Turn -- 10. Renato Rosaldo, Lessons from the Space between Languages: Notes on Poetry and Ethnography -- 11. Stephanie Newell, Researching the Cultural Politics of Dirt in Urban Africa -- Paul Youngquist, Accidental Histories: Among the Maroons of Jamaica -- Debra A. Castillo, Engagement and Pedagogy: Traveling with students in Chiapas, Mexico.
Keywords: Literature-Philosophy.; AREA STUDIES; Literature, Modern-20th century; Literary Theory